Kebijakan Moratorium Kapal Eks–Asing dalam Menangani Illegal Unreported and Unregulated (Iuu) Fishing di Perairan Indonesia Periode 2014 – 2016 - William Putri, Natasha Isabella Rossana; Windiani, Reni (Journal of International Relations, 2020)
This research seeks to explain then Indonesian Maritime Affairs and Fisheries Minister Susi Pudjiastuti's policy to ban foreign vessels from entering the country's waters between 2014 and 2016, as the country was trying to solve its Illegal, Unreported and Unregulated (IUU) fishing problem. Indonesia was suffering losses not only in terms of economy but also the environment as a consequence of the IUU fishing problem. More importantly, it posed a threat to the country's sovereign rights in its waters. As a result, President Joko Widodo's grand vision of making the country as so-called Global Maritime Fulcrum (GMF) was put to doubt by analysts and scholars alike. By approaching the problem with a realist analytical framework, this research focuses on how Indonesia was trying to curb IUU fishing cases by imposing a moratorium on foreign vessels in order to protect its environment and sovereignty. Using data both from primary and secondary sources, this research finds that the moratorium policy succeeded in creating deterrent effect on the perpetrators and lowering the number of foreign vessels entering the country's waters and thus preventing the number of IUU fishing cases from rising. Furthermore, this research finds that Indonesia managed to secure its fish stocks, to protect the ecosystem in its seas and to help local fishermen to prosper.